1981
DOI: 10.1021/ja00414a010
|View full text |Cite
|
Sign up to set email alerts
|

Mercaptide-chelated protoheme. A synthetic model compound for cytochrome P-450

Abstract: Although static, spectroscopic properties of such model systems are not affected by this excess base (RS"), dynamic properties could be greatly affected as they are with other bases such as (4) (a) Tang, S.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0
1

Year Published

1982
1982
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(15 citation statements)
references
References 0 publications
0
14
0
1
Order By: Relevance
“…This is similar to the hallmark Soret band of CO adduct of cytochrome P450 at 450 nm and typical of CO adducts ferrous porphyrin complexes bearing a thiolate axial ligand. 32,40,41 Complex 9 has several absorption bands in the visible region at 510, 577, and 647 nm, which shifts to 567, 617, and 699 nm in the CO complex ( Figure 2, inset). Note that the absorption maxima of the CO complex slowly shifts to 425 nm (t 1/2 ∼ 5 min), suggesting protonation of the thiolate ligand under these conditions as is known for several thiolate bound heme active sites.…”
Section: A Homogeneousmentioning
confidence: 99%
“…This is similar to the hallmark Soret band of CO adduct of cytochrome P450 at 450 nm and typical of CO adducts ferrous porphyrin complexes bearing a thiolate axial ligand. 32,40,41 Complex 9 has several absorption bands in the visible region at 510, 577, and 647 nm, which shifts to 567, 617, and 699 nm in the CO complex ( Figure 2, inset). Note that the absorption maxima of the CO complex slowly shifts to 425 nm (t 1/2 ∼ 5 min), suggesting protonation of the thiolate ligand under these conditions as is known for several thiolate bound heme active sites.…”
Section: A Homogeneousmentioning
confidence: 99%
“…One of these complexes carries ') Presented in part at the ' a 'S--bridge ' [20], the others contain 'S--tails' of various chain-length and structure, e.g. 5 [21] [22]. It was shown that these compounds form CO complexes, displaying the characteristic split Soret band (380 and 450 nm; calculated 325 and 430 nm [23]) of the native cytochrome P-450.…”
mentioning
confidence: 99%
“…It is interesting to note that, in the related but sterically less rigid systems of Battersby et al [20] and Traylor et al [22], removal of the protecting group at the S-atom was carried out only after reduction of Fe(II1). In the system of Collman and Groh [21] (see 5), this problem was circumvented by 'direct insertion' of Fe(I1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Bacterial cytochrome PA40 induced by camphor (PA45R,), isolated from Pseudomonas putida, catalyzes both the S-exohydroxylation of camphor and the exo-epoxidation of dehydrocamphor (3) in the presence of oxygen, NADH, and two additional protein components (putidaredoxin and NADH putidaredoxin reductase) that supply the P-450 with the necessary two electrons required for the overall reaction. One feature that distinguishes cytochrome P450 from other b-type hemoproteins is the apparent presence ofan axially bound thiolate ligand to the heme iron (4).. Thiolate coordination is thought to be responsible for the unusual spectral properties of the P450 enzymes in comparison to nitrogen-coordinated hemoproteins such as hemoglobin and horseradish peroxidase (5)(6)(7)(8)(9). Recent (11,12).…”
mentioning
confidence: 99%